The Effect of Brand Authenticity on Brand Love, Brand Attitude, and Brand Trust in Uniqlo Product Consumers - Nuravira Biruwintari; Aflit Nuryulia Praswati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study investigates the impact of brand genuineness on brand fondness, brand discernment, and brand reliability among Uniqlo patrons. The research examines how brand genuineness influences these factors and whether brand discernment and reliability mediate this relationship. Additionally, it considers potential moderating variables such as demographics and purchase frequency. Utilizing a descriptive quantitative approach, data were collected through an online questionnaire from 224 respondents and analyzed using PLS-SEM. This method was chosen to provide a robust statistical examination of consumer perceptions and interactions with the brand. The findings reveal that brand genuineness significantly influences brand discernment, reliability, and fondness. Moreover, brand reliability demonstrates a stronger mediation effect on brand fondness compared to brand discernment. These results highlight the critical role of authenticity in consumer-brand relationships. This study contributes to marketing literature by reinforcing the importance of brand genuineness in building consumer trust and loyalty. It also offers practical insights for brand strategists aiming to enhance authenticity and foster deeper emotional connections with consumers. The findings underscore that brand genuineness is essential in cultivating consumer allegiance and confidence in the Uniqlo brand.